2019
DOI: 10.1038/s41598-018-37416-7
|View full text |Cite
|
Sign up to set email alerts
|

Inter-digital capacitors with aerosol-deposited high-K dielectric layer for highest capacitance value in capacitive super-sensing applications

Abstract: Inter-digital capacitors (IDCs) with aerosol-deposition (AD) high-k dielectric layer were compared via simulation and measurements of bare IDCs and AD IDCs at room temperature and subjected to a post-annealing process for realizing capacitive super-sensing applications. IDCs with thin AD films can provide higher capacitive intensity and improvements for other dielectric performances. Therefore, IDC patterns with AD high-k dielectric layers were fabricated by varying the finger widths and gap. Moreover, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Annealing can reduce the deposition process‐induced stress in AD‐BT films, indicated by a change in lattice distortion and hence, peak position. This is in good agreement with our previous work and can be observed in other oxide ceramic AD films 38,48–50 . Moreover, a change in peak width can be correlated to the change in crystallite size.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Annealing can reduce the deposition process‐induced stress in AD‐BT films, indicated by a change in lattice distortion and hence, peak position. This is in good agreement with our previous work and can be observed in other oxide ceramic AD films 38,48–50 . Moreover, a change in peak width can be correlated to the change in crystallite size.…”
Section: Resultssupporting
confidence: 93%
“…This is in good agreement with our previous work and can be observed in other oxide ceramic AD films. 38,[48][49][50] Moreover, a change in peak width can be correlated to the change in crystallite size. However, for AD-BT films, it was found that annealing at 500 • C does not induce significant change in crystallite size.…”
Section: Effects Of Thermal Treatmentmentioning
confidence: 99%
“…For making an efficient DIDC-based biosensor, dielectric constant, charge distribution, and conductivity of DIDC were observed to be of high significance. Importantly, the changes in these sensing parameters correspond to the capacitive reactance of the DIDC. ,, In this research, we envisioned a capacitance immunosensor composed of anti-SARS-CoV-2 Abs functionalized via 1-ethyl-3-(3-dimethylaminopropyl)­carbodiimide– N -hydroxy succinimide (EDC-NHS) coupling on the GrO-DIDC-based SiO 2 substrate . In this process, EDC-NHS (cross-linker) was attached via covalent bonds onto the GrO substrate for the functionalization of anti-SARS-CoV-2 Abs.…”
Section: Functionalization and Detection Of Sars-cov-2 Spike (S1) Pro...mentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32] Furthermore, a variety of sensors was published using powder aerosol deposited functional films. [33][34][35][36][37][38] A more detailed description of the aerosol deposition process, its deposition mechanism, and the resulting film properties can be found in overview articles of Akedo's group 39,40 and of our group. 2 Developments in the past decade pointed towards a better understanding of the deposition mechanism, 10,[41][42][43][44] possible applications, 36,40,[45][46][47][48] and a scale-up of the spray process.…”
Section: Raw Materialsmentioning
confidence: 99%
“…Already realized electrochemical applications are photocatalytic ceramics 11–17 like TiO 2 , GaN–ZnO, and BiVO 4 , as well as energy storage and conversion devices like fuel cells, 18–22 thermoelectric generators, 23,24 and batteries 25–32 . Furthermore, a variety of sensors was published using powder aerosol deposited functional films 33–38 . A more detailed description of the aerosol deposition process, its deposition mechanism, and the resulting film properties can be found in overview articles of Akedo's group 39,40 and of our group 2…”
Section: Introductionmentioning
confidence: 99%